2011
DOI: 10.1111/j.1471-4159.2011.07422.x
|View full text |Cite
|
Sign up to set email alerts
|

The fatty acid oxidation product 15‐A3t‐Isoprostane is a potent inhibitor of NFκB transcription and macrophage transformation

Abstract: Fatty acids such as eicosapentaenoic acid (EPA) have been shown to be beneficial for neurological function and human health. It is widely thought that oxidation products of EPA are responsible for biological activity, although the specific EPA peroxidation product(s) which exert these responses have not yet been identified. In this work we provide the first evidence that the synthesized representative cyclopentenone IsoP, 15-A3t-IsoP, serves as a potent inhibitor of lipopolysaccharide-stimulated macrophage act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…Unsaturated FFAs have been found to be able to protect against oxidative stress by reducing lipid peroxidation and inhibiting the inflammatory pathway NF-B, which can lead to endothelial cell activation (9,11,15,39). Thus OA may prevent oxidative stress in LSEC that decreases ERK1/2 activity (38,48), thereby allowing cells to resume cell survival and proliferation after day 3.…”
Section: Discussionmentioning
confidence: 99%
“…Unsaturated FFAs have been found to be able to protect against oxidative stress by reducing lipid peroxidation and inhibiting the inflammatory pathway NF-B, which can lead to endothelial cell activation (9,11,15,39). Thus OA may prevent oxidative stress in LSEC that decreases ERK1/2 activity (38,48), thereby allowing cells to resume cell survival and proliferation after day 3.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a study of liver tissue in culture, oxidized EPA inhibited the inflammatory NF- κ B pathway [34]. This may be mediated by n-3 derived isoprostanes, as these peroxides have been shown to be biologically active, inhibiting macrophage NF- κ B activation in tissue culture [35]; and affecting vascular and platelet function [10]. It is not yet clear whether these effects are important in vivo ; however, they provide evidence for a divergence of effects when n-3 LC-PUFAs are oxidized.…”
Section: Are Oxidized Omega-3 Oils Efficacious?mentioning
confidence: 99%
“…The effects of oxidation on the biological effects of these oils may be complex, there could be both beneficial [10, 34, 35] and harmful effects. Thus, long-term safety studies of marine oil are required, looking at appropriate disease outcomes and surrogates and relating these to the oxidative state.…”
Section: Are Oxidized Omega-3 Supplements Harmful?mentioning
confidence: 99%
“…Altogether, the results reinforced the hypothesis that F 4 -NeuroPs could contribute to the anti-atherogenic effects of DHA. In parallel, several in vitro experiments showed that EPA and DHA-related isoprostanes (namely 15-A 3t -IsoP, J 3 -IsoP, A 4 /J 4 -NeuroP and 4-F 4t -NeuroP) possessed potent anti-inflammatory properties linked notably to the inhibition of the NFκB and/or Nrf-2 pathways [76][77][78][79]. However, contrasting outcome was found in supplementation of RTT patients with n-3 PUFA from fish oil in which plasma free F 4 -NeuroPs concentrations were lower when compared to controls.…”
Section: Bioactive Lipids and Potential Signaling Moleculesmentioning
confidence: 99%